Idiopathic non-familial Acro-osteolysis: A rare case report - Pijush K Datta; Sanjay Ghosh; Abhishek De (Wolters Kluwer Medknow Publications, 2012)
A 25-year-old woman patient presented with shortening of fingers with racket nails and numerous yellowish papules over the hands and forearms for 21 years. X-ray of the hands revealed destructive osteolytic changes in all the terminal phalanges. Skin biopsy from the yellowish papules showed epidermal proliferation, perivascular mononuclear infiltrate, thickening of dermal collagen, septal fibrosis and loss of adipocytes mimicking sclerodermatous changes in the dermis and hypodermis. The patient did not have any history of similar illness in the family or occupational exposure to vinyl chloride. After excluding all other possibilities of acral-osteolysis, we diagnosed the case as idiopathic non-familial variety of acro-osteolysis. This is a rare entity characterized by terminal resorption of fingers, sometimes associated with Raynaud's phenomena and yellowish cutaneous papules.